The Effect of Intelligence, Leg Muscle Strength, and Balance Towards The Learning Outcomes of Pencak Silat with Empty-Handed Single Artistic - Aridhotul Haqiyah; Mulyana Mulyana; Widiastuti Widiastuti; Dani Nur Riyadi (JETL (Journal of Education, Teaching and Learning), 2017)
This study aims to Determine the effect of intelligence, leg muscle strength, as well as the balance towards the learning outcomes of pencak silat empty-handed single artistic on the Physical Education students of Islamic University 45 Bekasi. The research method is a survey, and the analysis technique is path analysis. This research held in Islamic University 45 Bekasi with 122 people of population. The sampling technique used is random sampling, then a sample of this research is 60 people. The instruments used are a rubric 4 scale (very good, good, enough and less) of the learning outcomes of pencak silat emptyhanded single artistic, intelligence test with IST (Intelligent Structure Test), leg muscle strength with instrument squat test, and test of balance by using the modified bass test of dynamic balance. Based the result of the data processing and analysis, the Conclusions are: : (1) Intelligence directly effect on the learningoutcomes of pencak silat empty-handed single artistic with ρy1  = 0.359, (2) Leg muscles strength directlyeffect on the learning outcomes of pencak silat empty-handed single artistic with ρy2 = 0.228, (3) Balance directly effect on the learning outcomes of pencak silat empty-handed single artistic with ρy3 = 0.356, (4) Intelligence directly effects on the balance with ρ31 = 0.662, and (5) Leg muscle strength directly effectson the balance with ρ32 = 0.298.